1988
DOI: 10.1037/0022-0167.35.3.222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of therapist response modes in brief psychotherapy.

Abstract: We examined therapist response modes in 127 sessions of eight cases of brief psychotherapy with experienced therapists and anxious-depressed clients. Response modes had a significant effect on immediate outcome, with self-disclosure, interpretation, approval, and paraphrase being the most helpful response modes. Therapist response modes were then examined in conjunction with therapist intentions and client experiencing in the previous speaking turn, both of which accounted for more of the variance in immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
263
3
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(275 citation statements)
references
References 27 publications
7
263
3
2
Order By: Relevance
“…For example, Hill et al (1988) found that clients rated therapists as more helpful when therapists increased their level of self-disclosure, although the frequency of this intervention remained low. Furthermore, in addition to finding that clients reported having more insight as a consequence of TSD, Knox, Hess, Petersen, and Hill (1997) found that clients perceived therapists as more real and human, which improved the quality of the therapeutic relationship and helped clients feel reassured and normal.…”
Section: General Use Of Tsdmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hill et al (1988) found that clients rated therapists as more helpful when therapists increased their level of self-disclosure, although the frequency of this intervention remained low. Furthermore, in addition to finding that clients reported having more insight as a consequence of TSD, Knox, Hess, Petersen, and Hill (1997) found that clients perceived therapists as more real and human, which improved the quality of the therapeutic relationship and helped clients feel reassured and normal.…”
Section: General Use Of Tsdmentioning
confidence: 99%
“…For example, some evidence suggests that such disclosures may have no effect (Beutler & Mitchell, 1981;Hill et al, 1988) or a negative effect (Braswell, Kendall, Braith, Caery, & Vye, 1985) on client 3 Burkard, Knox, Groen, Perez, & Hess treatment. Of most interest, Hill and Knox (2002) found that the operational definition of or methods for assessing TSD were often problematic in studies in which neutral or negative effects were found, perhaps accounting for the findings.…”
Section: General Use Of Tsdmentioning
confidence: 99%
“…More recently, cross-cultural counseling theorists have also suggested that TSD be used to convey the therapist's sensitivity to cultural and racial issues, which may result in an increase of trust, greater perception of therapist credibility, positive implications for client outcomes. For example, Hill et al (1988) found that clients rated therapists as more helpful when therapists increased their level of self-disclosure, although the frequency of this intervention remained low. Furthermore, in addition to finding that clients reported having more insight as a consequence of TSD, Knox, Hess, Petersen, and Hill (1997) found that clients perceived therapists as more real and human, which improved the quality of the therapeutic relationship and helped clients feel reassured and normal.…”
mentioning
confidence: 99%
“…For example, some evidence suggests that such disclosures may have no effect (Beutler & Mitchell, 1981;Hill et al, 1988) or a negative effect (Braswell, Kendall, Braith, Caery, & Vye, 1985) on client treatment. Of most interest, Hill and Knox (2002) found that the operational definition of or methods for assessing TSD were often problematic in studies in which neutral or negative effects were found, perhaps accounting for the findings.…”
mentioning
confidence: 99%
“…Research has demonstrated that closed questions are perceived as not very helpful when working with clients (Hill, Helms, Tichenor, et al, 1988), and closed questions were the most common intervention used in the current study. It is likely that the novice level of the therapists involved in the study was related to their reliance on closed questions; however, it is also possible that the online setting made it awkward to use other counseling skills.…”
Section: Implications For Online Counseling Practicementioning
confidence: 99%